IMPLEMENTASI PAJAK RUMAH MAKAN TERHADAP PENDAPATAN ASLI DAERAH KOTA PROBOLINGGO PADA MASA COVID 19 (PERATURAN DAERAH KOTA PROBOLINGGO NO. 2 TAHUN 2011) - Ridhoi, Fahmi (Universitas Tribhuwana Tungga Dewi, 2023)
Abstract : Efforts to realize people's welfare so that it is more just and equitable must continue to be increased, economic growth must be increased through real efforts in the form of improving income and increasing people's purchasing power. Restaurant tax is one of the regional taxes that makes a large contribution to Regional Original Revenue (PAD). The restaurant tax has great potential because at present many entrepreneurs are establishing restaurants in various places, especially in tourism areas, densely populated residential areas, office areas, school and university areas. The focus of the research is the Government's Role in the Allocation of Regional Original Income (PAD), namely restaurant taxes as an effort to increase development. The results of the study show that with the realization of